Reasoned opinion on the modification of the existing MRLs for trifloxystrobin in spring onions and globe artichokes - European Food Safety Authority (EFSA Journal, 2012)
In accordance with Article 6 of Regulation (EC) No 396/2005, Italy, hereafter referred to as the Evaluating Member State Italy (EMS Italy), received an application from Bayer CropScience to modify the existing MRL for trifloxystrobin in globe artichokes. Belgium, hereafter referred to as the Evaluating Member State Belgium (EMS Belgium), compiled an application to modify the existing MRL for trifloxystrobin in spring onions. In order to accommodate the intended uses of trifloxystrobin on these crops, the Evaluating Member States proposed to raise the existing MRLs for trifloxystrobin from the limit of quantification (LOQ) of 0.02 mg/kg to 0.2 mg/kg in globe artichokes and to 0.1 mg/kg in spring onions. The evaluation reports were drafted in accordance with Article 8 of Regulation (EC) No 396/2005 and were submitted to the European Commission and forwarded to EFSA. The available residue trials data confirm the MRL proposals for trifloxystrobin in spring onions and globe artichokes as derived by the Evaluating Member States. Adequate analytical enforcement methods are available to control the residues of trifloxystrobin in the commodities under consideration. Based on the risk assessment results, EFSA concludes that the intended use of trifloxystrobin on spring onions and globe artichokes will not result in a consumer exposure exceeding the toxicological reference value and therefore is unlikely to pose a consumer health risk.